Seasonal Changes and Relationships in Training Loads, Neuromuscular Performance, and Recovery and Stress State in Competitive Female Soccer Players - Ai Ishida; Ai Ishida; Caleb D. Bazyler; Adam L. Sayers; Michael H. Stone; Michael H. Stone; Jeremy A. Gentles (Frontiers Media S.A., 2021)
Background: The purpose of this study was to examine seasonal changes in training load (TL), neuromuscular performance, subjective recovery, and stress state, and to investigate the relationships between acute and chronic TL and neuromuscular performance in competitive female soccer players.Methods: Nine competitive female soccer players (20.0 ± 1.7 years; 60.3 ± 6.3 kg; 164.0 ± 5.8 cm) completed the Short Recovery and Stress Scale and the countermovement jump (CMJ) with polyvinyl chloride pipe (CMJ0) and 20 kg barbell (CMJ20) at 2-3 h before 1st match (NC1), 6th match (NC2), 9th match (C1), and 15th match (C2) of the competitive season. TL included total distance, high-speed running, and PlayerLoad. Acute and chronic TL was calculated by using the average of 2 days (D2), 7 days (D7), and 21 days (D21) prior to four different match play.Results: Significant decreases were found from NC1 to C1 in D7 total distance [p = 0.03, Cohen's effect size (dz) = 1.40]. D7 total distance and PlayerLoad significantly decreased from NC to C1 and C2 (p = 0.001-0.01, dz = 1.40-1.72). Significant increases were observed from NC1 to C1 in CMJ0 jump height (p = 0.03, dz = 1.40), (p = 0.021, dz = 1.44), and peak power (p = 0.03, dz = 1.32). Significant negative correlations were observed for D7 total distance and CMJ0 jump height (p = 0.02, r = 0.79) and peak power (p = 0.03, r = 0.71) at C2, while significant positive correlations were observed at C1 for D7 PlayerLoad and CMJ0 jump height (p = 0.02, r = 0.80).Conclusion: Polyvinyl chloride pipe (CMJ0) jump height and peak power may increase from preseason to the midcompetitive season. Seasonal variations may affect the relationships between D7 TL and CMJ0 performance.